Foreword - Matthew S Sachs (Fungal Genetics Reports, 2000)
The 47th edition of the Fungal Genetics Newsletter contains articles and notes on a wide variety of topics. As usual, the Aspergillus and Neurospora bibliographies are included, as is the most recent Fungal Genetics Stock Center mailing list.